Pendidikan Karakter sebagai Pendidikan Otak perspektif Kajian Neurosains Spiritual - Dahuri Dahuri (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2023)
Character education should encourage students to understand behavior based on knowledge (cognitive), appreciate religious values in behavior (affective), and lead to the realization of religious values in the practice of life based on divine values (spiritual). Islamic education has for many years focused on studying Aql (the human mind) so that very little mentions the problem of the brain as neuroscience and has not fully studied it. The teachings of Islam appear to be doctrinally pedagogical and empirically irrational. So that many Muslim scientists are less interested in discussing the brain because their understanding of the human mind is limited and has weaknesses. The state, represented by the Ministry of Education, formulates 4 character values which are used as a reference for the application of character to students in schools, namely honesty (sourced from the heart), intelligence (starting from thinking), toughness (starting from sports) and caring (referring to the sense and intention). Developing all values is certainly not an easy thing, so it is necessary to prioritize instilling values in students according to their level of understanding not only cognitively but more towards spiritual values. The author uses library research, by collecting data to explain the solution to a problem which is principally guided by critical analysis and is rooted in related and appropriate literature. This research shows the results that if a person uses the brain properly and naturally in thinking, then he is able to exude good character so that spiritual values are encompassed in his daily life leading to an increase in faith and piety to his God because he is more diligent and devoted in worship.